PERAN NAZHIR DALAM PEMBERDAYAAN WAKAF (TINJAUAN TERHADAP STRATEGI PEMBERDAYAAN WAKAF BADAN WAKAF ALQURAN DAN WAKAF CENTER) - Tiswarni, Tiswarni (Universitas Islam Negeri Raden Intan Lampung, 2014)
Abstract: Nadzir Role in The Empowerment of Endowment (Overview Of Empowerment Strategy Endowments Waqf Board Qur’an and Endowments Center). This study discusses the empowerment of waqf made by BWA and WATER. Attempts to explore how far Nazhir’s role in empowering the waqf property, particularly in the BWA and WATER. Aims to investigate strategies pursued by both institutions in the waqf empowerment. This research can be categorized in the field of Islamic law and social institutions research. The findings of the study: the strategies launched by BWA are creating Quranic mushaf endowments program and making an innovative endowmentprograms, utilizing support from others, creating networking in waqf, and distributeswaqf and its benefits on the right target. As well as WATER also uses several strategies: making the endowments for the benefit programs, establishing new enterprises, utilizing the support received, creating networking and cooperation in waqf, and distributing waqf investment returns on the right target.Keywords: nazhir, empowerment, waqf (endowments)Abstrak: Peran Nazhir dalam Pemberdayaan Wakaf (Tinjauan Terhadap Strategi Pemberdayaan Wakaf Badan Wakaf Alquran dan Wakaf Center). Studi ini membahas pemberdayaan wakaf yang dibuat oleh Badan Wakaf Alquran (BWA) dan Wakaf Center (WATER). Upaya untuk mengeksplorasi seberapa jauh peran Nazhir dalam memberdayakan properti wakaf, khususnya di BWA dan WATER. Bertujuan untuk menyelidiki strategi yang ditempuh oleh kedua lembaga dalam pemberdayaan wakaf. Penelitian ini dapat dikategorikan dalam bidang hukum Islam dan lembaga penelitian sosial. Temuan penelitiannya adalah strategi yang diluncurkan oleh BWA menciptakan Program Wakaf Alquran dan membuat program-program yang inovatif abadi, memanfaatkan dukungan dari orang lain, menciptakan jaringan wakaf, mendistribusikan wakaf dan memanfaatkannya pada sasaran yang tepat. Sementara WATER juga menggunakan beberapa strategi yakni membuat wakaf untuk program manfaat, mendirikan perusahaan baru, memanfaatkan dukungan yang diterima, menciptakan jaringan dan kerjasama dalam wakaf, dan mendistribusikan hasil investasi wakaf pada sasaran yang tepat.Kata Kunci: Nazhir, pemberdayaan, wakaf wakaf